The Clinical Observation of Acupuncture Combined With Antiemetic Drugs in the Prevention and Treatment of CINV in Breast Cancer Patients - Kong, Fanming; Wang, Ziwei; Wang, Na; Zhao, Lu; Mei, Qingyun; Yu, Yongchao; Zhang, Dou; Li, Xiaojiang; Jia, Yingjie (Frontiers in Oncology, 2022)
Abstract Objective: Chemotherapy-induced nausea and vomiting (CINV) is a common and distressing side effect. Now, we did this study aimed to explore the effectiveness of acupuncture combined with antiemetic drugs in controlling CINV among postoperative breast cancer patients. Methods: The clinical data of 81 postoperative breast cancer patients admitted to the First Affiliated Hospital of Tianjin University of Traditional Chinese Medicine from January 2021 to December 2021 were reviewed. Then, we will divide those people who received AC chemotherapy into two groups. Retrospective analysis efficacy of the antiemetic drugs, such as dexamethasone, aprepitant or fosaprepitant, 5-hydroxytryptamine type 3 receptor antagonist so on, in combination with or without acupuncture for CINV. The primary endpoints were total, acute, and delayed nausea and vomiting grade and remission rate. Safety and overall patient quality of life were secondary endpoints. Results: (1) In the control and acupuncture group, the frequency of vomiting was 7.3% vs 0%, the frequency of nausea was 9.8% vs 5%, respectively, in the 0-24h group. the frequency of vomiting and nausea was 19.5% vs12.5%, and the frequency of nausea was 26.8% vs 12.5%, respectively, in the 24-120h group through the incidence of nausea and vomiting during the whole observation period was: Compared with the control group, the incidence of nausea and vomiting in the experimental group decreased, and the incidence of nausea decreased, with statistical significance (P< 0.05). (2) Compared with the control group, the ECOG score in the experimental group was significantly improved (P< 0.01), and the incidence of adverse events, abdominal (P＞ 0.05), distention (P= 0.049), and diarrhea (P= 0.044), was also decreased. Conclusions: Acupuncture combined with antiemetics can better reduce the incidence of CINV, especially in controlling the occurrence of nausea has clear advantages. In addition, It also improves the quality of life of patients and reduces the incidence of adverse reactions to antiemetic drugs.